Islam is a foreign country : American Muslims and the global crisis of authority - Grewal, Zareena (New York : New York University Press, 2014)
'In Islam Is a Foreign Country, Zareena Grewal explores some of the most pressing debates about and among American Muslims: what does it mean to be Muslim and American? Who has the authority to speak for Islam and to lead the stunningly diverse population of American Muslims? Do their ties to the larger Muslim world undermine their efforts to make Islam an American religion? Offering rich insights into these questions and more, Grewal follows the journeys of American Muslim youth who travel in global, underground Islamic networks. Devoutly religious and often politically disaffected, these young men and women are in search of a home for themselves and their tradition. Through their stories, Grewal captures the multiple directions of the global flows of people, practices, and ideas that connect U.S. mosques to the Muslim world. By examining the tension between American Muslims' ambivalence toward the American mainstream and their desire to enter it, Grewal puts contemporary debates about Islam in the context of a long history of American racial and religious exclusions. Probing the competing obligations of American Muslims to the nation and to the umma (the global community of Muslim believers), Islam is a Foreign Country investigates the meaning of American citizenship and the place of Islam in a global age. Zareena Grewal is Assistant Professor of American Studies and Religious Studies at Yale University and Director for the Center for the Study of American Muslims at the Institute for Social Policy and Understanding'--
Introduction: unmapping the Muslim world -- Islam is a foreign country: mapping the global crisis of authority -- Islamic utopias, American dystopia: Muslim moral geographies after the great migration -- Imaginary homelands, American dreams: Sunni moral geographies after 1965 -- Retrieving tradition: pedological forms and secular reforms -- Choosing tradition: women student-travelers between resistance and submission -- Transmitting tradition: the constraints of crisis -- Muslim reformers and the American media: the exceptional umma and its emergent moral geography -- Epilogue: American Muslims and the place of dissent.
Includes bibliographical references and index.
Keywords: Muslim youth -- United States -- Attitudes; Muslim youth -- Religious life -- United States; Islam -- United States; Ummah (Islam); Social integration -- United States; United States -- Ethnic relations